Singapore : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Singapore. (IMF Staff Country Reports; Country Report, 2021)
Singapore entered the COVID-19 pandemic with sizable policy space and robust economic policy frameworks, yet facing longer-term challenges. The economy has been severely impacted by the pandemic, but a bold, comprehensive, and coordinated policy package has helped cushion the economic fallout. Following a record contraction in the first half of 2020, activity has rebounded, and growth is projected to strengthen to 6 percent in 2021, underpinned by a recovery in domestic demand and a positive contribution from net exports. The uncertainty surrounding the outlook is larger than usual.